2008
DOI: 10.1007/s00592-008-0060-9
|View full text |Cite
|
Sign up to set email alerts
|

A single test procedure to diagnose gestational diabetes mellitus

Abstract: Universal screening for gestational diabetes mellitus (GDM), detects more cases and improves maternal and offspring prognosis. Of all the screening tests, World Health Organization (WHO) procedure is simple and cost effective; the only disadvantage is that the pregnant woman has to come in the fasting state to undergo oral glucose tolerance test (OGTT). Hence, we undertook a study to elucidate a test that is casual and reliable to diagnose GDM. A total of 800 pregnant women underwent 75-g glucose challenge tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
86
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(88 citation statements)
references
References 7 publications
2
86
0
Order By: Relevance
“…These results were also found by V. Seshiash et al who found the incidence in urban areas (17.8%) was nearly double in rural areas (9.9%). 4 The incidence of GDM increases with increasing parity. Pregnancy is a diabetogenic stage which causes stress on the Beta cells to produce more insulin.…”
Section: Discussionmentioning
confidence: 99%
“…These results were also found by V. Seshiash et al who found the incidence in urban areas (17.8%) was nearly double in rural areas (9.9%). 4 The incidence of GDM increases with increasing parity. Pregnancy is a diabetogenic stage which causes stress on the Beta cells to produce more insulin.…”
Section: Discussionmentioning
confidence: 99%
“…8 Anjalakshmi C et al performed this 75 gm OGCT and compared it with 75 gm GTT and found statistically no significant difference. 9 Seshiah et al in 2005 recommended this one step 75 gm OGCT in diagnosing GDM with 2-hour PPG ≥140mg/dl as per WHO criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Yet another study suggests a similar procedure in that, a pregnant woman after undergoing preliminary clinical examination in the prenatal clinic is given a 75 g oral glucose load, without regard to the time of the last meal and venous blood sample is collected at 2 h for estimating PG by the GOD-POD method. GDM is diagnosed, if 2 h PG is > 140 mg/dL [13]. Performing this test procedure in the nonfasting state is rational, as glucose concentrations are affected little by the time since the last meal in a normal glucose tolerant woman, whereas it will, in a woman with GDM [14].…”
mentioning
confidence: 99%
“…Therefore, this procedure assumes clinical relevance as WHO criteria based on glucose concentration 2 h after 75 g glucose load was able to correctly identify subjects with GDM. This single step procedure serves as both screening and diagnostic test for GDM, and is simple, economical and feasible [13]. The 2 h PG>140 mg/dl has got clinical significance as both short term and long term morbidity in the offspring of GDM mothers occurs above this glycemic level [16].…”
mentioning
confidence: 99%
See 1 more Smart Citation